Nature provides valuable sanitation services - Willcock, Simon; Parker, Alison; Wilson, Charlotte; Brewer, Timothy R.; Bundhoo, Dilshaad; Cooper, Sarah; Lynch, Kenneth; Mekala, Sneha; Mishra, Prajna Paramita; Rey, Dolores; Welivita, Indunee; Venkatesh, Kongala; et al. (Elsevier, 2021)
Much previous research shows that safe disposal of human waste has a positive impact on human wellbeing, while preventing the degradation of ecosystems. However, to date, the role that ecosystems themselves play in treating human waste has been largely neglected. We conceptualize the role nature plays in treating human waste—acting as a pipeline and/or treatment plant. We estimate that nature is treating ~41.7 million tons of human waste per year worldwide, a service worth at least 4.4 ± 3.0 billion USD year−1. We demonstrate the opportunities and challenges of quantifying these “sanitation ecosystem services,” using 48 cities across the globe as a worked example. In highlighting this, we are not marginalizing the vital role of engineered infrastructure, but instead are promoting better understanding of how engineered and natural infrastructure interact within a circular economy. This is a promising route for further research and may allow adaptive design and management, reducing costs, and improving effectiveness and sustainability.
Keywords: water; WASH; natural sanitation; nature-based solution; ecosystem service